In VivoEvaluation of the Protective Capacity of Different Gloves Against Hair Dyes - Annarita Antelmi; Magnus Bruze; Erik Zimerson; Malin Engfeldt; Caterina Foti; Cecilia Svedman (International Journal of Occupational and Environmental Medicine, 2019)
Hairdressers are taught to use gloves when dyeing hair. We wanted to study what gloves are recommendable for other common hair dye substances than p-phenylenediamine, such as toluene-2,5-diamine sulphate and 2‐methoxymethyl‐p‐phenylenediamine. The gloves used in professional salons and the gloves commonly sold with hair dyes for home-use were investigated. 7 volunteers previously allergic to toluene-2,5-diamine sulphate and p-phenylenediamine were tested in vivo with an open chamber test system to examine the permeation of chemicals through gloves (vinyl, nitrile and polyethylene), mimicking the real use condition of permanent hair dyes. The nitrile gloves used gave excellent protection with all four hair dyes tested. A good capacity of protection was found with the polyethylene glove, supplied with the package of a home-use hair dye, when tested with the same hair dye. The advice to hairdressers is to choice nitrile gloves when using the permanent hair dyes currently available on the market.
Keywords: Hair Dyes